Effect of ethanol on the antimicrobial properties of chlorhexidine over oral biofilm - Marks Duarte, Pedro Henrique; Silva, Paula Barcellos da; Rosa, Ricardo Abreu da; Montagner, Francisco; Hungaro Duarte, Marco Antonio; Kuga, Milton Carlos [UNESP]; Reis So, Marcus Vinicius (Wiley-Blackwell, 2018)
The aim of this study was to evaluate the effect of 95% ethanol irrigation, with 5 or 10 min of action, on the antibacterial properties of 2% chlorhexidine (CHX), on oral biofilm, evaluated with confocal laser scanning microscopy (CLSM). Oral biofilm development was induced in 80 sterilized bovine dentin blocks, distributed in two groups (5 or 10 min) and 4 subgroups, according to time and the solution used: Saline (SALINE5, SALINE10); Saline followed by CHX (SALINE/CHX5, SALINE/CHX10); Ethanol (ETHANOL5, ETHANOL10), Ethanol followed by CHX (ETHANOL/CHX5, ETHANOL/CHX10). The surface of the block was dyed with Live/Dead((R)) BacLight. Images from different areas were analyzed by BioImage L program. The total biovolum (mu m(3)), biovolum of live cells (green), percentage of live cells of the thickness of the biofilm visualized in CLSM and on surface biofilm were evaluated. Total biovolum and biovolum of living cells showed similar results among the different groups (p>.05). The percentage of living cells in total thickness of the biofilm also was similar among the groups (p>.05), except ETHANOL5, SALINE/CHX10, ETHANOL10, and ETHANOL/CHX10 that showed lower percentage than SALINE5 (p<.05). The ETHANOL10 and ETHANOL/CHX10 also showed lower percentage of living cells than ETHANOL/CHX5 and SALINE10 (p<.05). In relation to biofilm surface, SALINE/CHX5, SALINE/CHX10, ETHANOL5, ETHANOL10, ETHANOL/CHX5, and ETHANOL/CHX10 showed a lower percentage of living cells percentage than SALINE5 and SALINE10 groups (p<.05). Therefore, ethanol has no effect on antimicrobial properties of 2% chlorhexidine, prior when used as endodontic irrigating solution.
Keywords: confocal microscopy; endodontics; root canal irrigants